2015
DOI: 10.4028/www.scientific.net/kem.641.105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plasma Gases on the Structure and Properties of WC-CrC-Ni Coatings

Abstract: The effect of plasma gases (argon, helium) on the structure and properties of the WC-CrC-Ni coatings deposited at the graphite substrate has been investigated. The coatings were deposited by plasma spraying method in equipment Cham Pro –Thermal Spray Systems produced by Sulzer company. The microstructure of coatings were investigated by light microscopy (MO) and scanning electron microscopy (SEM). The performed investigations have been shown that with the increasing of amounts of argon and reducing volumes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The type of charge powder can also influence the coating properties, including the coating compactability. It was found that nanometric charge powder contributes to the lowest porosity of coatings [6]. The evaluation of wettability by liquid copper (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The type of charge powder can also influence the coating properties, including the coating compactability. It was found that nanometric charge powder contributes to the lowest porosity of coatings [6]. The evaluation of wettability by liquid copper (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Future studies will focus on the increase of thermal conductivity by the decrease of porosity, proper selection of process parameters, chemical composition of coatings and type of charge powder. The nanometric microstructure of coatings can also contribute to an improvement of this feature [6].…”
Section: Discussionmentioning
confidence: 99%
“…The corrosion resistance of this type of coating was investigated by Murariu et al [25]. Richert et al analysed the influence of LPPS plasma spraying parameters on the microstructure of WC-CrC-Ni coating [26]. The mechanical properties of HVOF--sprayed coatings were investigated by Jonda and Latka [27].…”
Section: Introductionmentioning
confidence: 99%
“…The plasma sprayed coatings are characterized by higher porosity and lower hardness [8][9]. The investigations showed that the thermal process parameters significantly influenced the coating properties, such as: distance to the substrate, velocity of particles in plasma stream, size of the sprayed powder particles, residence time of the powder in the air and used gases [10][11][12]. From this point of view, the proper selection of process parameters is very important to obtain the coatings with the defined properties and structure.…”
Section: Introductionmentioning
confidence: 99%